Teacher Performance and Student Character in Islamic Schools: Case of History Learning in Spain's Pandemic Time - Castillo, Ruth (Indonesian Journal of History Education, 2023)
This research aims to analyze teacher performance and student character in Islamic schools by highlighting the case of history learning in Spain during the Pandemic. This research uses descriptive qualitative methods. Research location in an Islamic-based school. The data sources in the research are informants, consisting of the deputy head of curriculum, history teacher, and student representatives from each class, learning activities, and documents. The results of this research show that planning for online history learning in Islamic-based schools is good, but teachers need to improve their competence and ability to adapt to technology; The role of history teachers in the process of cultivating character in pandemic conditions through distance learning is very limited. Interaction between teachers and students is very limited. Meanwhile, in distance learning, the assessment of the character of each student is seen from assignments, monitoring outside class hours, and communication with parents; Student responses to the role of history teachers in cultivating character through distance learning are different for each student. Student responses are influenced by students' interest in history subjects, as well as the methods and media used by teachers to attract students' attention.